1988
DOI: 10.3109/08941938809141077
|View full text |Cite
|
Sign up to set email alerts
|

Swine as Models in Experimental Surgery

Abstract: The use of swine in surgical research has undergone a dramatic increase in recent years, due to decreasing availability of dogs as surgical models and a renewed interest in the porcine model based on anatomic and physiologic characteristics. This article reviews the issues involved in selection of swine as experimental surgical subjects including procurement considerations, anesthetic selection, housing methods, and anatomic and physiologic characteristics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
112
0
2

Year Published

1999
1999
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(117 citation statements)
references
References 9 publications
2
112
0
2
Order By: Relevance
“…The knowledge of anatomical variations is important for radiological and surgical procedures in humans and animals due to its practical and theoretical significance for experimental research and surgical practice in experimental and domestic animals (Swindle et al 1988, Krotscheck et al 2007). Particular attention has been paid to the dissective or angiographical study of the visceral vessels because of the variations noticed among various animal species.…”
Section: Introductionmentioning
confidence: 99%
“…The knowledge of anatomical variations is important for radiological and surgical procedures in humans and animals due to its practical and theoretical significance for experimental research and surgical practice in experimental and domestic animals (Swindle et al 1988, Krotscheck et al 2007). Particular attention has been paid to the dissective or angiographical study of the visceral vessels because of the variations noticed among various animal species.…”
Section: Introductionmentioning
confidence: 99%
“…There are many similarities between a porcine animal model and humans regarding metabolic and cardiovascular function [168,169,170]. The model has human hemodynamic characteristics [171] and similar coronary anatomy compared with human cardiac anatomy, with the exception of the left azygous vein, which enters the coronary sinus rather than the precava [168,169,170]. However, in addition to the limitation that all animals were anesthetized as required by our ethics committee, the present studies have other limitations.…”
Section: The Experimental Model Of Cprmentioning
confidence: 93%
“…Using a swine model, it was demonstrated that the duration of resuscitation may be extended throughout the use of a vasoactive drug prior to rescue countershock [167]. There are many similarities between a porcine animal model and humans regarding metabolic and cardiovascular function [168,169,170]. The model has human hemodynamic characteristics [171] and similar coronary anatomy compared with human cardiac anatomy, with the exception of the left azygous vein, which enters the coronary sinus rather than the precava [168,169,170].…”
Section: The Experimental Model Of Cprmentioning
confidence: 99%
“…The technical aspects of his discussion, such as selection of the animal with the skin best replicating human skin, are beyond the scope of this thesis. However, this discussion, along with similar model critiques by others (Sternbach and Rosen 1977;Woakes and Cranwell 1977;Kaplan and Timmons 1979;Mattsson et al 1980;Loew 1982;Gay 1983;Swindle 1983aSwindle , 1983bSwindle , 1984Swindle , 1986Swindle and Smith 1988;Kerrigan etal. 1986;Horneffer et al 1986;Zrunek et al 1988;Boothe and Hartsfield 1990;Powell et al 1991;Chapman et al 1994;Cameron et al 1994;and Chapman et al 1996) are invaluable to trauma trainers who must consider such issues in their own model selection.…”
Section: Animal Modelsmentioning
confidence: 99%
“…The use of the pig has largely replaced the use of the dog as the model of choice for experimental surgery. Although the pig is an excellent model for many experimental and training procedures, this change is largely a reflection of budgetary issues and mounting social and regulatory pressures (Woakes and Cranwell 1977;Kerrigan et al 1986;Horneffer et al 1986;Cameron et al 1994;Swindle 1983aSwindle , 1983bSwindle , 1984Swindle , 1986Swindle and Smith 1988;Anders et al 1989;Gormley 1990;and Gholson et al 1990).…”
Section: Animal Modelsmentioning
confidence: 99%